A prospective study in the Australian petroleum industry. I. Mortality. Issue 8 (August 1991) - Christie, D; Robinson, K; Gordon, I; Bisby, J
Abstract : This paper reports the mortality experience of employees of the Australian petroleum industry from 1981 to 1989. Two surveys by personal interview incorporated more than 15, 000 employees representing 92% of the eligible population. Subjects were included in the analysis after completing five years of service in the industry. At the time of this report the cohort does not include sufficiently large numbers of women for useful analysis; results presented are restricted to men. By 31 December 1989, 76, 529 person-years of observation had accumulated for male mortality with 241 deaths. The standardised mortality ratio (SMR) analysis showed a favourable mortality experience for most causes with overall cancer rates slightly lower than those of the national population. Whereas deficits were seen in some cancer sites, notably lung cancers (SMR 0.5, 95% confidence interval (95% CI) 0.3-0.8), mortality for lymphohaematopoietic cancers, notably leukaemia (SMR 1.6, 95% CI 0.6-3.4) suggested increased risk. The SMR for cancers of the pleura was 3.9 (95% CI 0.8-11). Two of the three cases seen had previous employment, however, in industries with likely exposure to asbestos.